Increased Tenascin-C expression contributes to cardiac dysfunction and fibrosis in Duchenne muscular dystrophy. (3rd October 2022) - Kiss, A; Szabo, P L; Ebner, J; Hilber, K; Abraham, D; Costantino, S; Paneni, F; Nikhanj, A; Kashyap, N; Ouadit, G Y; Podesser, B K
Abstract: Introduction and aims: Cardiac fibrosis is characterized by the net accumulation of extracellular matrix (ECM) proteins in the cardiac interstitium and contributes to cardiac contractile dysfunction. In Duchenne muscular dystrophy (DMD), cardiomyopathy develops as a result of a dystrophin deficiency causing fibrofatty replacement of the myocardium, however the underlying mechanisms are not fully understood. There is a growing collection of evidence that ECM proteins, including Tenascin C (TN-C), plays a maladaptive role in left ventricular (LV) remodelling and cardiac fibrosis in ischemic heart disease. The aims of our study were 1) to assess TN-C levels, fibrosis and cardiac dysfunction in DMD patients, and 2) to clarify the role of TN-C in cardiovascular dysfunction and fibrosis using male mdx (n=10) and mdx TN-C KO mice (n=8). Results: In male patients with DMD (n=18) and age matched controls (n=12) undergoing cardiac MRI, we detected greater myocardial fibrosis than in control hearts. In addition, we observed an elevation of TN-C plasma levels [median concentration (3.55); interquartile range (0.61–7.43) ng/mL] in DMD patients, and its expression negatively correlated to LV ejection fraction (EF) [median LVEF (45); interquartile range (37.5–51.5) %]. Male wt, mdx and mdx TN-C KO age-matched (10 months) mice were used. Transthoracic echocardiography was performed and fibrosis was assessed on cardiac tissue sections. Wire myography was used to assess vascular endothelial function. To explore the signalling pathways contributing to cardiac fibrosis, human cardiac fibroblasts (hCFs) were treated with recombinant human TN-C or TGF-β and gene expression and epigenetic regulation of NF-kB/p65 were assessed. Mdx mice showed significantly increased cardiac fibrosis which was accompanied with markedly elevated TN-C level in cardiac tissue and plasma compared to wt animals (p<0.05, respectively). Moreover, TN-C level in plasma correlated positively with the degree of cardiac dilation in dystrophic mice. In addition, vascular endothelial function was notably impaired in mdx mice. In contrast, we observed preserved vascular function in mdx- TN-C KO mice, this was accompanied by a significant reduction in cardiac fibrosis in compared to age-matched mdx mice (p<0.05, respectively). hCFs treated with TN-C or TGF-β showed increased collagen and α-SMA expressions which could be prevented by application of siRNA against TN-C. In addition, both TN-C and TGF-β caused p65/NF-κB promoter demethylation and subsequently triggered pro-inflammatory and pro-fibrotic signalling, which could be reversed by applying p38 MAPK inhibitor in hCFs. Conclusion: TN-C is a critical component of cardiac fibrosis and cardiac dysfunction in DMD. The activation of NF-κB p65 signalling pathway may play a role in TN-C induced fibrosis. Thus, TN-C may be a mediator and potential target for therapy in DMD-associated cardiovascular complications. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Österreichische MuskelforschungFWF - Austrian Science Found P 35878